Huge anharmonic effects in superconducting hydrides and transition metal dichalcogenides. Issue 12 (26th September 2014) - Errea, Ion; Calandra, Matteo; Mauri, Francesco
<x xml:space="preserve">Abstract</x> Even if the harmonic approximation describing the vibrations of atoms in solids suffices to interpret experimental measurements in many occasions, it can completely break down when the displacements of the atoms exceed the range in which the harmonic potential is valid. The stochastic self‐consistent harmonic approximation method is precisely devised to calculate theoretically vibrational properties in strongly anharmonic solids in which the harmonic theory fails. We apply this method to palladium hydrides and 2H‐NbSe<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbhd6v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives>, two strongly anharmonic systems that exemplify the importance of anharmonic effects in metallic hydrides and transition metal dichalcogenides. First of all, we explain that the inversion of the isotope effect in palladium hydrides is a consequence of huge anharmonic effects. The temperature dependence of the phonon spectra in PdH, PdD, and PdT is also presented, where qualitative differences are predicted depending on the isotope. Secondly, we demonstrate that the high‐temperature 2H‐NbSe<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbhd59" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> structure is fully stabilized dynamically by anharmonicity. The softening with temperature of the acoustic longitudinal mode in 2H‐NbSe<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2jcbhd4r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2</alternatives> at the CDW momentum is predicted as well by our calculation.